On the Macroeconomic Determinants of the Long-Term Oil-Stock Correlation - Christian Conrad; Karin Loch; Daniel Rittler (University of Heidelberg, Department of Economics, 2012)
Using a modified DCC-MIDAS specification, we endogenize the long-term correlation between crude oil and stock price returns with respect to the stance of the U.S. macroeconomy. We find that variables which contain information on current and future economic activity are helpful predictors for changes in the oil-stock correlation. For the period 1993-2011 there is strong evidence for a counter cyclical behavior of the long-term correlation. For prolonged periods with strong growth above trend our model predicts a negative long-term correlation, while before and during recessions the sign changes and remains positive throughout the economic recovery. Our results strongly suggest that crude oil prices cannot be viewed as being exogenous with respect to the U.S. macroeconomy and explain the controversial results concerning the oil-stock relationship in previous studies.
urn:nbn:de:bsz:16-opus-131806
Keywords: C32; C58; Q43; 330; Oil-stock relationship; long-term volatility; long-term correlation; GARCH-MIDAS; DCC-MIDAS; Ölpreis; Börsenkurs; Wirkungsanalyse; Konjunktur; Wirtschaftswachstum; Schätzung; USA